Deep Integration in Trade Agreements : Labor Clauses, Tariffs, and Trade Flows - Robertson, Raymond (World Bank, Washington, DC, 2021)
Deepening preferential trade agreements extend coverage to social issues, including labor clauses. While there is a long history of debate over the intent of labor clauses, less is known about the impact of labor clauses. Recent studies show that labor clauses improve working conditions, but the impact on trade flows is still debated. Existing studies do not include a full set of fixed effects (to control for endogeneity and unobserved confounding factors), other dimensions of deep agreements that could be correlated with labor clauses (tariffs and other “deep” clauses), and pseudo-Poisson maximum likelihood estimation. This paper combines all three with additional robustness checks. While the estimated effect of trade agreements is positive overall, the estimated marginal relationship between labor clauses and trade volume is generally negative but varies with the type of clauses. Freedom of Association, Forced and Child Labor, and International Labor Standards are consistently associated with higher trade flows. Clauses that are more likely to eliminate illicit trade, including clauses related to discrimination, protection of working conditions, and third-party monitoring exhibit a negative marginal relationship with trade flows.